2022
DOI: 10.3389/fmicb.2022.1031101
|View full text |Cite
|
Sign up to set email alerts
|

Topically applied bacteriophage to control multi-drug resistant Pseudomonas aeruginosa-infected wounds in a New Zealand rabbit model

Abstract: Pseudomonas aeruginosa (P. aeruginosa) is a widespread, gram-negative, pathogenic bacterium that causes serious internal and external infections in humans and other animals. The increasing antibiotic resistance has complicated bacterial infection treatment, and current antibiotic therapies cannot cure all infections. Owing to this, bacteriophages (phages) have regained attention as potential therapeutics for bacterial infections. In this study, the phage “PaVOA” was isolated from hospital sewage and characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Several studies have evaluated the efficacy of topical bacteriophages in treating burn wounds, and the results have been promising [ [42] , [43] , [44] ]. There is also a study showed that the topically applied bacteriophage cocktail could reduce the bacterial load significantly in multi-drug resistant P. aeruginosa (MDR-PA) infected wounds in the New Zealand rabbit model, resulting in improved wound healing outcomes [ 45 ]. Following this, we isolated the lytic bacteriophages of P. aeruginosa and used them topically against this pathogenic bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated the efficacy of topical bacteriophages in treating burn wounds, and the results have been promising [ [42] , [43] , [44] ]. There is also a study showed that the topically applied bacteriophage cocktail could reduce the bacterial load significantly in multi-drug resistant P. aeruginosa (MDR-PA) infected wounds in the New Zealand rabbit model, resulting in improved wound healing outcomes [ 45 ]. Following this, we isolated the lytic bacteriophages of P. aeruginosa and used them topically against this pathogenic bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple bacteriophages are reportedly being explored for phage therapy for various manifestations of skin-associated pathogens. Support for clinical research comes from phage therapy success for skin infections of Mycobacterium chelonae and multiple-drug resistant (MDR) Pseudomonas aeruginosa [ 104 , 105 ]. Topical bacteriophage therapy targeting C. acnes has advanced to phase I clinical trials after displaying efficacy in reducing C. acnes abundance without significant safety concerns [ 106 ].…”
Section: Therapeutically Relevant Skin-microbiome-derived Compoundsmentioning
confidence: 99%
“…Wang et al. constructed a New Zealand rabbit skin infection model and treated it with a Pseudomonas aeruginosa phage, and found that phage treatment of skin infections was significantly more effective than antibiotic treatment, indicating that phages have great potential in treating skin infections ( Wang et al., 2022 ). In another clinical study, the authors combined phages with antibiotics to successfully treat MDR-PA infections caused after liver transplantation in young children, which provides new insights for the treatment of post-surgical bacterial infections ( Van Nieuwenhuyse et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%